ANALYSIS OF THE PHYTOCHEMICAL POTENTIAL OF Moringa oleifera LEAF TEA FORMULATION AND NATURAL SPICES AS AN ALTERNATIVE TO STUNTING PREVENTION - Angga Dwi Prasetyo; Moh. Taufik; Bertina Seviana Putri; A'ida Fajrin Najwa (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Stunting prevention efforts require a locally focused, nutrient-rich, and easily accessible approach. This study aims to analyze the phytochemical potential of moringa tea (Moringa oleifera) and various natural spices such as ginger, turmeric, lemongrass, and galangal as natural alternatives in stunting prevention. The research will be carried out from June to December 2024. The methods used include qualitative phytochemical tests to identify active compounds such as flavonoids, tannins, saponins, alkaloids, and terpenoids/steroids; the formulation of moringa leaf tea and natural spices; and a literature review and meta-analysis of the role of these bioactives in supporting the nutritional status and immune system of children. The results of the analysis showed that moringa tea and spices contain a variety of bioactive compounds with antioxidant, anti-inflammatory, and immunostimulant properties that have the potential to support optimal growth of children. Based on the results of meta-analysis and literature studies, it can be concluded that the phytochemical content of Moringa leaf tea has the potential to prevent stunting in mothers and children. Further research is needed to test the effectiveness of the formula and optimal dosage in clinical applications.